Pay for Performance, Performance Management, and Internal Promotional Opportunities of Human Resource Practices with Job Performance - Desa, Nasina Mat; Asaari, Muhammad Hasmi Abu Hassan (Canadian Center of Science and Education, 2020)
This study explores the relationship and the impact of pay for performance, performance management, and internal promotional opportunities of human resources practices toward task performance and contextual performance of job performance. The study was conducted on the electrical and electronics (E&E) engineers in the Bayan Lepas Free Trade Zone, Penang. Self-administered questionnaires were distributed through the E&E manufacturing companies’ human resource managers. A total of 1,100 questionnaires were distributed that adapted and adopted the research tools of Rhoades et al. on pay for performance, Allen et al. on performance management, Wayne et al. on internal promotional opportunities, Williams and Anderson on task performance, and Hochwarter et al. on contextual performance. A total of 181 were returned but 150 questionnaires were useable for this study. The engineers indicated that only the internal promotional opportunities had a relationship with task performance and contextual performance. On the other hand, pay for performance and performance management had a relationship with contextual performance but not with task performance. Moreover, engineers indicated that none of the human resource practices, namely pay for performance, performance management, and internal promotional opportunities, had an impact on both of their job performance, namely task performance and contextual performance.